SEM-Based Decision Support Model for Cost-Quality Impact Analysis on a Fast-Track Project’s Duration - Sultan, Mustafa; Hassan, Ishtiaq; Safdar Gardezi, Syed Shujaa (Civil Engineering Journal, 2025)
The fast-track technique was introduced to mitigate time overruns and meet project deadlines; however, limited understanding exists regarding how cost and quality-related decisions influence the duration of such projects. This study aims to analyze the impact of cost and quality variances on project duration, ultimately proposing a decision support model tailored for fast-track high-rise building projects. Data were collected from 159 respondents and analyzed using Structural Equation Modeling (SEM), through which four hypotheses were formulated. The findings reveal that both cost and quality variances significantly affect project duration, with quality variance also exerting a notable influence on project cost. Mediation analysis further demonstrated that cost variance serves as a statistically significant mediator between quality variation and project duration. The R² values of the proposed model indicate that 78.4% of the variation in project duration can be attributed to changes in cost and quality, while 72.9% of the variation in project cost is linked to quality changes. The Importance–Performance Map Analysis (IPMA) identified the early procurement of long-lead-time items, the adoption of a scope-freeze approach during the early design phase, and the over-design of facilities as the most critical and best-performing decisions. The model introduces novel β-values and confirms the statistically significant relationships among cost, quality, and time. Additionally, model validation metrics—including Q², RMSE, MAE, and CVPAT—demonstrated strong out-of-sample predictive power of the proposed framework.